Evolution of the diagnosis of malnutrition in adults: a primer for clinicians - Hegazi, Refaat; Miller, Anthony; Sauer, Abby (Frontiers in Nutrition, 2024)
During the last two decades, the definition, diagnosis, and management of malnutrition have significantly evolved. Malnutrition is generally defined as deficiencies, excesses, or imbalances in a person's intake of energy and/or nutrients. While malnutrition is associated with significantly increased risk of morbidity, mortality, and health care cost, it is often underdiagnosed both in healthcare and community settings. One contributing factor is the lack of a consensus on its definition and appropriate diagnostic indicators. In the current article, we review the evolution of frameworks for the diagnosis of malnutrition. Recently published consensuses by prominent clinical nutrition societies have established a trajectory for the uniform global diagnosis of malnutrition. Limiting the use of body mass index (BMI) as a diagnostic criterion while emphasizing the use of muscle mass enables a more consistent and accurate diagnosis of malnutrition in the clinical setting. Guidance for the unified methodology and terminology for diagnosing malnutrition, such as the one proposed in the current article will enable policy makers to systematically address the two faces of malnutrition, starvation-and disease-related malnutrition applicable to both pediatric and adult populations. Policies and programs that could address issues of food insecurity and scarcity as well as early diagnosis and management of disease-related malnutrition will empower better care of community nutrition.